If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying sqrt(x + 1) + -2 = sqrt(x + 3) + x Reorder the terms: qrst(1 + x) + -2 = sqrt(x + 3) + x (1 * qrst + x * qrst) + -2 = sqrt(x + 3) + x (1qrst + qrstx) + -2 = sqrt(x + 3) + x Reorder the terms: -2 + 1qrst + qrstx = sqrt(x + 3) + x Reorder the terms: -2 + 1qrst + qrstx = qrst(3 + x) + x -2 + 1qrst + qrstx = (3 * qrst + x * qrst) + x -2 + 1qrst + qrstx = (3qrst + qrstx) + x Add '-1qrstx' to each side of the equation. -2 + 1qrst + qrstx + -1qrstx = 3qrst + qrstx + -1qrstx + x Combine like terms: qrstx + -1qrstx = 0 -2 + 1qrst + 0 = 3qrst + qrstx + -1qrstx + x -2 + 1qrst = 3qrst + qrstx + -1qrstx + x Combine like terms: qrstx + -1qrstx = 0 -2 + 1qrst = 3qrst + 0 + x -2 + 1qrst = 3qrst + x Solving -2 + 1qrst = 3qrst + x Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-3qrst' to each side of the equation. -2 + 1qrst + -3qrst = 3qrst + -3qrst + x Combine like terms: 1qrst + -3qrst = -2qrst -2 + -2qrst = 3qrst + -3qrst + x Combine like terms: 3qrst + -3qrst = 0 -2 + -2qrst = 0 + x -2 + -2qrst = x Add '2' to each side of the equation. -2 + 2 + -2qrst = 2 + x Combine like terms: -2 + 2 = 0 0 + -2qrst = 2 + x -2qrst = 2 + x Divide each side by '-2rst'. q = -1r-1s-1t-1 + -0.5r-1s-1t-1x Simplifying q = -1r-1s-1t-1 + -0.5r-1s-1t-1x
| 5X+X+y+(y+29)=127 | | 3y+3x=0 | | 3n^2+37n-1360=0 | | 6(s-2)=5(s+10) | | 144=18n+45 | | 14+2(4s-3)=40 | | 3n-7=6n-2n | | 3/9=y/21 | | (8x+100)+(2x+50)=90 | | 6x-7/7x=6=x-3/x-2 | | 5y=4cosx+1 | | 4-7z=22+22 | | 8a^3-27= | | 4s+4t= | | 6x-17=2x+3 | | 8(x-3)=-7(x+2)+47 | | r-1=4+6r | | 32+8x=38+7x | | x*x+7x=11 | | 3x^(1/2)-13x^(1/4)-30=0 | | 0=16t^2+60t+4 | | -3=3(6x)+4x | | X^2x=24 | | 3x^1/2-13x^1/4-30=0 | | 6(n+3)=30 | | 7/3×13/8 | | 2/4y-1=1/4 | | y=16t^2+60t+4 | | b-3a= | | -4x7/-14 | | 7/3×13/8= | | -3(n+5)-5n=-5n-39 |